Analisis Morfofonemik Dialek Lamalera - Magi Krova, Magdalena (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
This research is entitled "Morphophonemic Analysis of Lamalera Dialect". This title was taken as research because the Lmalera dialect is the Lamaholot language and has its own identity in the form of vowel lengthening in the previous syllable. This morphophonemic work is determined on the influence of morphemes and phonemes as well as grammatical influence. The formulation of the problem in this study is how Lamalera morphophonemic which includes morpheme and phoneme effects and grammatical effects of Lamalera dialect. The purpose of this study is to find out the morphophonemic process of Lamalera dialect in the form of morpheme and phoneme effects and grammatical effects of Lamalera dialect. The method in this research uses the listening method and the chap method, while the data analysis technique in this research is descriptive. The reason the researcher uses this technique is a way used by researchers to process data which will then be descriptive in detail the results of observations of the data that has been collected. The conclusion of this study states that, nouns ending in the vowel /a/ will change to the nasal vowel /a^/ in the form of the second person singular owner. Lamalera dialect has a joint where -an changes into /a^/, there is also a morphophonemical change which is the lengthening of the vowel in the previous syllable. When due to other grammatical elements that follow the vowel changes /e^/ and /o/, the vowel changes /e^/ and /o/ in nouns. If the vowel /e"/ is preceded by another vowel, the morphophonemic changes will follow the pattern below: the final vowel /e"/ preceded by the vowel /a/ only takes a morphophonemic change to /i/.